Philippine corporate governance issues and reforms - Echanis, Erlinda S. (Philippine Management Review, 2006)
This paper describes the macro structure for corporate governance in Philippine firms and their impact on internal corporate governance. The paper also assesses the strengths and weaknesses of corporate governance reforms initiated by regulatory agencies in the Philippines. Selected cases of corporate governance failures in some firms in the Philippine financial services sector are also presented. Weaknesses in corporate governance mechanisms in these cases were categorized into : 1) decision processes; 2) violation of regulations; 3) weaknesses of regulatory agencies; and 4) financial reporting standards. The paper ends with some recommendations addressing some of these weaknesses and other necessary reforms to improve corporate governance in Philippine firms.